Oceanography of the Cape Verde Basin and Mauritanian Slope Waters - Pelegrí, Josep Lluís; Peña-Izquierdo, Jesús; Machín, Félix; Meiners, César; Presas-Navarro, Carmen (Springer, 2017)
35 pages, 23 figures The Cape Verde (CV) Basin is the site of fronts and currents that function as both barriers and connectors between the tropical and subtropical oceans. Here we review former studies and analyze historical, satellite and numerical data in order to portray the oceanography of the CV Basin, with emphasis on its eastern boundary—the Mauritania Slope (MS) Ocean. This is complemented with the analysis of novel hydrographic data from the continental slope. The CV Basin is a dynamic region, forced by seasonally varying winds that drive both coastal and offshoreupwelling, the latter linked to the Guinea Dome. Its circulation is controlled by the seasonally changing Dome to the south and southwest, with associated cyclonic currents, and by the CV frontal system to the north, with along-slope flow convergence and offshore export. The MS Ocean is the site of the Poleward Undercurrent, undistinguishable from the offshore Mauritania Current during winter–spring. The predominant thermocline water–mass is the nutrient-rich South Atlantic Central Water, almost pure in upper layers (100–300 m)—providing for the high primary production in the entire region—and with substantial North–Atlantic contribution in its lower part (300–550 m)—in what constitutes the poorly–ventilated low oxygen minimum zone; nutrient concentrations keep increasing with depth until the core of the AntarcticIntermediate Waters (700–800 m). The CV Basin holds both the highest primary production and lowest oxygen concentrations for the entire tropical and subtropicalNorth Atlantic gyres, with extensive implications on fisheries, but yet remains a largely unexplored oceanic region This research has been supported by the VA-DE-RETRO project (CTM2014-56987) with funding from the Spanish government Peer Reviewed